Role of community pharmacists in providing oral health advice in the Eastern province of Saudi Arabia - Hamad Al-Saleh; Thamir Al-Houtan; Khalid Al-Odaill; Basel Al-Mutairi; Mohammed Al-Muaybid; Tameem Al-Falah; Muhammad Ashraf Nazir (Elsevier, 2017)
Objective: To determine the frequency of patients seeking oral health advice and willingness of community pharmacists to provide oral health information in the Eastern Province of Saudi Arabia. Methods: A cross-sectional study with sample size (n = 332) of randomly selected community pharmacists across the province. The questionnaire comprised of 25 questions divided into 3 sections. Frequency distributions of different categorical variables were calculated and Pearson's chi-square tests were performed to compare categorical variables. Statistical significance was determined at p-value <0.05%. SPSS version 22 was used for statistical analyses. Results: Of the 332 pharmacists, 279 agreed to participate in the study, yielding a response rate of 84%. About 71% of pharmacists provided less than 30 oral health advices and 29% of them gave ≥30 oral health advices daily. Oral ulcer (64.2%), dental pain (59.5%) and bleeding gums (54.5%) were the three most common oral conditions encountered by the pharmacists. More pharmacists (90%) were approached for advice about tooth whitening products, tooth brush and mouth wash in large cities compared with 66.7% of pharmacists in small cities of the province. Lack of interaction with dental professionals was recognized the most important barrier to providing oral health services to the clients. Almost one third (35.8%) had formal oral health training in their undergraduate program and only 26.5% of them were always confident in providing oral health advices. Majority (93.5%) of respondents recognized their important role in providing oral health advices and 98.2% were enthusiastic to provide oral health information. Conclusions: Community pharmacists are approached frequently for oral healthcare advices. Majority of them had no oral health training. Almost all of them were willing to provide oral health information in the community. It is essential to provide continuous oral health education to the pharmacists to better serve oral health needs of the community. Keywords: Community pharmacist, Oral health advice, Oral problems, Saudi Arabia